Initial Antihypertensive Treatment Strategies and Therapeutic Inertia: Evidence From a Large Population-Based Cohort. Issue 4 (October 2018) - Rea, Federico; Corrao, Giovanni; Merlino, Luca; Mancia, Giuseppe
Abstract : In many hypertensive patients, treatment is not upgraded despite lack of blood pressure control because of therapeutic inertia. Information is limited, however, on the extent of this phenomenon in real-life medicine. We studied 125 635 patients (age 40–85 years) from the Lombardy region (Italy) who started antihypertensive treatment with 1 drug (n=100 982) or a 2-drug fixed-dose or free combination (n=24 653). A log-binomial regression model was used to estimate the prevalence ratio of combination therapy in relation to the initial treatment strategy. In the initial monotherapy group, patients under drug combinations were 22%, 27%, 32%, and 36% at 6 months, 1, 2, and 3 years later. In the initial combination treatment group, the corresponding percentages were 85%, 82%, 79%, and 78%. This translated into a markedly greater covariate-adjusted propensity of being under a multidrug prescription throughout the follow-up: 3.92 (95% CI, 3.84–4.00) after 6 months and 3.18 (3.12–3.25), 2.56 (2.51–2.60), and 2.23 (2.19–2.27) after 1, 2 and 3 years of treatment. In a propensity score analysis, initial 2-drug combination treatment was also associated with significant reductions in the risk of death (−20%, 11% to 28%) and hospitalization for cardiovascular events (−16%, 10% to 21%) compared with initial monotherapy. Thus, in real life, a large number of patients prescribed initial monotherapy fails to move to combination treatment, as recommended by guidelines. This implies that therapeutic inertia frequently prevents proper treatment uptitration, thereby playing a major role in the low rate of hypertension control that exists worldwide. Abstract : Supplemental Digital Content is available in the text.